Peripheral neuropathy & neuropathic pain into the light - Said, G. (Gerard) (Tfm Pub., 2015)
Peripheral neuropathy is a common medical condition, the diagnosis of which is often protracted or delayed. It is not always easy to relate a neuropathy to a specific cause. Many people do not receive a full diagnosis, their neuropathy often being described as 'idiopathic' or 'cryptogenic'. It is said that in Europe, one of the most common causes is diabetes mellitus but there are also many other known potential causes. The difficulty of diagnosis, the limited number of treatment options, a perceived lack of knowledge of the subject - except in specialised clinics, the number of which are limited - all add to the difficulties which many neuropathy patients have to face.